Computing with words approach for fuzzy group decision-making - Tarmudi, Zamali; Md. Tap, Abu Osman; Abdullah, Mohd Lazim (2010)
This paper discusses an alternative computation approach for the fuzzy linguistics evaluation process that utilises the concept of ‘computing with words’. Three steps were established under the linguistic information; i) identification of the linguistic term set with its semantic, ii) choosing the appropriate aggregation operator of linguistic information, and iii) derivation and selection of the best alternative through aggregation and exploitation phases. A numerical example was employed to demonstrate the feasibility of the proposed approach. The result shows that the approach is highly beneficial in terms of applicability and user friendly in a decision framework.